1977
DOI: 10.2307/249019
|View full text |Cite
|
Sign up to set email alerts
|

MIS Problems and Failures: A Socio-Technical Perspective, Part II: The Application of Socio-Technical Theory

Abstract: Many of the problems arjd failures of Management Information Systems (MIS) and Management Science/Operations Research (MS/OR) projects have been attributed to organizational behavioral problems. The millions of dollars organizations spend on MIS and MS/OR development are of little benefit because systems continue to fail. Steps can be taken to understand and solve these behavioral probiems. This article argues that in most oases these behavioral problems are the result of inadequate designs. These bad designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
211
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(218 citation statements)
references
References 6 publications
6
211
0
1
Order By: Relevance
“…In this paper, the Socio-Technical Systems (STS) theory [11,12] is invited as a theoretical foundation. From the literature review, the social aspects are essential in determining the tourists' sustainable values [23].…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the Socio-Technical Systems (STS) theory [11,12] is invited as a theoretical foundation. From the literature review, the social aspects are essential in determining the tourists' sustainable values [23].…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Instead, many of the tourism systems have been developed in a way that makes tourists skip the interaction with other stakeholders, such as full-automated service systems [34] or information kiosks [35]. In this regard, STS perspective suggests a smart tourism design opportunity that enables the joint-optimization of various subsystems, such as social subsystems, technical subsystems, and environmental subsystems [11,12,36]. With the objective of finding balanced values for all of those systems, there can be an increasing possibility of having efficient STD applications that support more synergetic values from stakeholders and the interconnected subsystems [37,38]; such objective is a primary goal of smart tourism systems.…”
Section: The Socio-technical Systems (Sts) Theorymentioning
confidence: 99%
“…However, this model was found to focus more on the role of IT in organisational transformation rather than on role allocation. Since cloud migration affects both technology and people, the sociotechnical theory of Bostrom and Heinen (1977) was considered. Closer examination revealed that it concentrates only on providing guidelines from a system design approach.…”
Section: Organisational Theorymentioning
confidence: 99%
“…The rapid acceleration of technological diffusion confronts BISE researchers, who usually study technological innovations from the perspective of socio-technical systems (Bostrom and Heinen 1977). Work systems are conceptualized as an interplay of tasks, technologies, and people (vom Brocke and Rosemann 2014), systems ''in which human participants and/or machines perform work (processes and activities) using information, technology, and other resources to produce specific products/services for specific internal and/or external customers'' (Alter 2013, p. 75).…”
Section: Introductionmentioning
confidence: 99%